2006
DOI: 10.1590/s1678-77572006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of oral rehabilitation with removable partial dentures after five years

Abstract: Most removable partial denture (RPD) wearers are satisfied with their prostheses, but the factors that influence satisfaction and acceptance are still not determined.Objective:This study explored technical, biological, and satisfaction variables for the functioning of RPDs after five years, and compared the evaluation by the patient and by the clinician.Materials and Methods:Fifty adults (39 females, 11 males) were reexamined after five years of RPD service. Data were collected through clinical examination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 25 publications
(34 reference statements)
5
34
2
4
Order By: Relevance
“…The following aspects related to overdenture rehabilitation were evaluated (annex 2): -The condition of the acrylic portion of the teeth and of the base, classified as "requiring intervention" or "not requiring intervention" (18); -Base adaptation, classified as "adapted" or "not adapted" (19); -Occlusion, classified as "satisfactory" or "unsatisfactory" (20); -Retention, classified as "excellent", "good" or "poor" (18); -Stability, classified as "excellent", "good", or "poor" (20).…”
Section: Clinical Examinationmentioning
confidence: 99%
“…The following aspects related to overdenture rehabilitation were evaluated (annex 2): -The condition of the acrylic portion of the teeth and of the base, classified as "requiring intervention" or "not requiring intervention" (18); -Base adaptation, classified as "adapted" or "not adapted" (19); -Occlusion, classified as "satisfactory" or "unsatisfactory" (20); -Retention, classified as "excellent", "good" or "poor" (18); -Stability, classified as "excellent", "good", or "poor" (20).…”
Section: Clinical Examinationmentioning
confidence: 99%
“…Parece que embora os indivíduos do género feminino tenham uma menor força muscular comparativamente aos do género masculino, essa força muscular é compensada por uma melhor coordenação e atividade sensorial por parte dos indivíduos do género feminino. 22 Neste estudo, um dos critérios de inclusão para os portadores de prótese parcial removível bimaxilar, foi o tempo de uso da prótese, embora o intervalo definido varie entre os 6 meses e os 5 anos, esse intervalo de acordo com estudos anteriores 23,24 parece não influenciar os resultados. A maioria das PPR's continuam a apresentar uma boa retenção e estabilidade após 5 anos de utilização.…”
Section: Discussionunclassified
“…A maioria das PPR's continuam a apresentar uma boa retenção e estabilidade após 5 anos de utilização. 23,24 Por outro lado, um exame clínico prévio foi realizado neste estudo de forma avaliar a estabilidade e retenção das PPR's dos participantes. As PPR's que apresentavam algum tipo de deslocamento vertical e/ou horizontal foram excluídas deste estudo.…”
Section: Discussionunclassified
“…Periodic checkup and oral hygiene measures of RPDs' users are essential to improve periodontal health and prosthesis longevity [17]. In contrary, Cosme et al, reported that there is no relation between oral hygiene and prosthesis [5,18]. As the MCs in intimate contact with oral mucosa, poor oral hygiene may increase the incidence of caries, Plaque accumulation, and periodontal diseases in RPD users.…”
Section: Hygienementioning
confidence: 99%
“…Clinically, RPD can increase the risk of plaque, gingivitis, and caries especially root ones, in patients who wear them; however, the risk of periodontitis is not obviously increased by them [18,61]. In a study done by Janaina et al, it was concluded that RPDs en-OPEN ACCESS http://scidoc.org/IJDOS.php hanced tooth mobility, diminished prevalence of caries and did not induce the fractures of abutments [62].…”
Section: Gingival and Periodontal Conditionsmentioning
confidence: 99%